kinetic agility relationship with accurately perform the forehand kick for table tennis beginners - A. D. Haider Abdul-ameer; A. D. Atheer Khaleel Ibrahim (الرياضة المعاصرة, 2019)
through the experience of the researchers as a instructor in the Baghdad Karkh/ 3, and through the contributions of his team in competitions, the researcher noted that there is a decline in the level of performance, which led to the reason for the decline in the agility, therefore, the researcher found it necessary to study this, and work to find the relationship between the most important used skills is the fore Hand Stroke and the agility that interfere with the performance of the skill, the researcher used the descriptive approach appropriate to the nature of the problem researched, the research sample was chosen as governorate Karkh / 3's players and their number was (8) players, tests were conducted and processing the results of appropriate by statistical means have been reached and there is a significant correlation between agility and accuracy of fore hand stroke, based on the conclusions of researcher recommended that attention capacity motor and conduct further studies around in other sports and on different samples